The effect of different physical therapy procedures in ultramarathons - Priscila dos Santos Bunn; Bruno de Souza Terra; Márcio Puglia Souza; Viviane Pereira de Souza Amaral; Allan Inoue Rodrigues; Kevin Alexander Barreto Magno; Daniel de Souza Alves; Elirez Bezerra da Silva (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: To analyze the effects of physical therapy procedures in reducing acute pain in runners. A second aim was to investigate the impact of weather conditions on the number of physical therapy visits during the Ultramarathon Rio24 h. Methods: This retrospective study was performed at the Physical Education Center Admiral Adalberto Nunes (CEFAN). Medical records were analyzed. The participants were athletes that were attended by the Physical therapy team during three editions of the Ultramarathon Rio24 h. The variation in the Visual Analog Scale score (VAS) before and after each treatment were analyzed. After the evaluation procedure, another professional had decided the best procedure for the assessed athlete: massotherapy, cryotherapy by immersion, or stretching. An ANOVA was performed to assess which procedures produce pain reduction immediately after the procedure. Results: A total of 1,995 care services (228 in women) were performed in 602 athletes (84 women). Analyzing the treatments that used only one modality (n = 512 visits), the final pain decreased significantly over the initial pain for the three treatments. It was verified that massotherapy, cryotherapy, and stretching promote significant intragroup differences, with no intergroup differences. The environmental conditions were not associated with the number of visits. Conclusion: Massotherapy, cryotherapy, and stretching are effective treatments for acute pain reduction during ultramarathons. The weather conditions are not associated with the number of physical therapy visits.